1991
DOI: 10.1111/j.1349-7006.1991.tb01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Transplantable Tumors by Repeated Subcutaneous Injections of Natural and Synthetic Vitamin E in Mice and Rats

Abstract: Natural vitamin E and synthetic vitamin E (dl/‐α‐tocopheryl acetate) were tested for their tnmorigenicity in rodents. Transplantable tumors, at the site of injection, were induced by repeated injections of these compounds in two strains of mice, NFS/N and C57BL/6N × C3H/He Fl, and in a strain of rats, Fischer 344. Natural vitamin E was tumorigenic in both strains of female mice only when injected with soya oil. In contrast, dl‐α‐tocopheryl acetate alone was capable of inducing tumors in Fischer 344 rats. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…a-T functions effectively as an inhibitor of lipid peroxidation and inhibits nitrosation when assessed in short-term assays (43,44,55); however, simultaneous formation of a nitrosating agent from reaction with NO2 suggests that long-term protection from genotoxic deamination reactions may be incomplete. This may explain enhanced tumor formation when a-T is administered to animals at high doses (17,18). Nitta et al (18) observed an inflammatory response at the site oftocopherol injection, suggesting that generation of free radicals by invading macrophages may have contributed to tumor formation.…”
Section: Materials and Methods Chemicals Morpholine A-t And -T-t Smentioning
confidence: 99%
See 1 more Smart Citation
“…a-T functions effectively as an inhibitor of lipid peroxidation and inhibits nitrosation when assessed in short-term assays (43,44,55); however, simultaneous formation of a nitrosating agent from reaction with NO2 suggests that long-term protection from genotoxic deamination reactions may be incomplete. This may explain enhanced tumor formation when a-T is administered to animals at high doses (17,18). Nitta et al (18) observed an inflammatory response at the site oftocopherol injection, suggesting that generation of free radicals by invading macrophages may have contributed to tumor formation.…”
Section: Materials and Methods Chemicals Morpholine A-t And -T-t Smentioning
confidence: 99%
“…This may explain enhanced tumor formation when a-T is administered to animals at high doses (17,18). Nitta et al (18) observed an inflammatory response at the site oftocopherol injection, suggesting that generation of free radicals by invading macrophages may have contributed to tumor formation.…”
Section: Materials and Methods Chemicals Morpholine A-t And -T-t Smentioning
confidence: 99%
“…In additional unpublished studies in our laboratory, topical applications of a-tocopherol 5 days a week to initiated high risk mice previously treated with UVB for 5 months enhanced the formation of skin tumors. In addition, the growth of tumors transplanted into mice, rats, or chickens was stimulated when the animals received multiple injections of vitamin E [Kline and Sanders, 1989;Nitta et al, 1991].…”
Section: Inhibitors Of Carcinogenesis In One Experimental Model May Smentioning
confidence: 99%
“…On the other hand, every antioxidant is in fact, a redox agent, protecting against reactive oxygen species in some circumstances and promoting free radical or secondary reactive oxygen species generation in others. Indeed, an excess of these antioxidants elevates the incidence of cancer (Nitta et al 1991;Omenn et al, 1996). Solovieva et al reported that antioxidants, ascorbic acid (Solovieva et al, 2007) and dithiothreitol (Solovieva et al, 2008), exhibit cytotoxicity via H 2 O 2 generation.…”
Section: Catalytic Decomposition Of Hydrogen Peroxide By Metal Nanopamentioning
confidence: 99%
“…(Yamashita et al, 1998;Murata & Kawanishi, 2000). Indeed, an excess of these antioxidants elevates the incidence of cancer (Nitta et al, 1991;Omenn et al, 1996). A catalyst consisting of an inorganic stable material is not oxidized and does not generate secondary reactive oxygen species.…”
Section: Summary and Possible Mechanism Of Hydrogen Peroxide Decomposmentioning
confidence: 99%